Tracking of Actinobacillus actinomycetemcomitans in subgingival plaque of aggressive periodontitis patients - Supriya Kheur; Vinay K Hazarey; Atya Kapley; Hemant Purohit (Wolters Kluwer Medknow Publications, 2010)
Background: Actinobacillus actinomycetemcomitans is thought to be one of the etiological agents in aggressive periodontitis as well as indicated in various systemic diseases. Objective: To evaluate the prevalence of A. actinomycetemcomitans in the subgingival plaque of aggressive periodontitis patients. Study Design: Initially, under the selective growth conditions, the isolates were picked from the plaques and their identification was confirmed by polymerase chain reaction using primers specific for A. actinomycetemcomitans subgingival plaque of 15 patients diagnosed clinically and on radiographic criteria as aggressive periodontitis was inoculated on the Tryptic Soy agar with Bacitracin and Vancomycin culture media for 3-5 days under microaerophilic conditions. The positive colonies were selected based on biochemical tests for further analysis using reported primers for A. actinomycetemcomitans. Results: The results showed that 66.67% of aggressive periodontitis patients and 6.67% of control group of normal patients showed evidence of presence of A. actinomycetemcomitans in the subgingival microflora. Conclusion: This is the first study of its kind in an Indian population whereby almost all aggressive periodontitis patients showed evidence of A. actinomycetemcomitans.